RESÍDUOS DE CURTUMES: ESTUDO DAS TENDÊNCIAS DE PESQUISA - Godecke, Marcos Vinicius; Rodrigues, Marco Antonio Siqueira; Naime, Roberto Harb (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705779 Taking waste from tanneries as a research subject, this study identified the trends of theseinvestigations through the review of recent publications. Have been identified four factors:toxicity, treatment technologies, economic value and ecological efficiency. The analysis ofpublications showed that it is a fruitful field for further research in various scientific fields relatedto technical and management areas, besides of their combination in interdisciplinary scopes. Newstudies are necessary before the predominant framework of environmental depletion, low ecoefficiencyof industrial processes and incipient economic use of waste.